Lesbians In Makassar City: Analysis Of Social Construction In The City Context - Mario Mario (Educational Dynamics: International Journal of Education and Social Sciences, 2024)
The social construction of lesbians in Makassar City is greatly influenced by the social dynamics around them. The processes of externalization, objectification, and internalization experienced by lesbian individuals create space for the lesbian community to form more flexible and diverse identities and roles. Nevertheless, the challenges that lesbians face are related to social norms that often limit the expression of their identities, both in heterosexual contexts and within their own communities. Lesbians who choose to display a more feminine or masculine role, or conversely display a more neutral identity, demonstrate an effort to communicate and adapt to it.This research also reveals that there is a tension between the quest for acceptance by wider society and the search for space for freedom of self-expression. For some lesbians, the choice to appear in accordance with social expectations such as feminine or masculine appearance is a way to conform to existing norms, even though sometimes this does not reflect their true identity. On the other hand, lesbians who prefer not to be bound by labels and rigid gender roles show that they are trying to fight for freedom in defining their own relationships and identity. This research contributes to the understanding of how the social construction of lesbians is shaped and influenced by various social factors, culture, and personal experiences, as well as how lesbian individuals navigate their social world by forming a more flexible and evolving identity.